Charophytes: drivers of carbonate sedimentation, carbon sequestration and aquatic health - Pełechaty, Mariusz (Frontiers in Freshwater Science, 2025)
This review explores biomass production and CaCO3 precipitation by charophytes (Charophyta) and their environmental implications. A hypothesis was developed that charophytes play a substantial role in sedimentary processes and that the long-term deposition of CaCO3 in the sediments contributes significantly to the sequestration of excess carbon in bottom sediments. The study shows that, compared to angiosperms, many charophytes produce significantly greater dry mass. Tall and branchy species produce higher dry weight (DW) per individual but form sparser communities while smaller and slender charophytes can produce lower DW but tend to create very compact carpets that balance species-specific differences in dry mass production. While charophyte dry mass frequently exceeds 1 kg DW m−2 or even 2 kg DW m−2 in temperate climate, the study from Mediterranean climate reports charophyte DW can exceed 4.1 kg m−2 and in extreme cases be up to 11.5 kg m−2. Compared to angiosperms some charophytes are highly efficient in utilizing bicarbonate as a carbon source for photosynthesis and precipitating calcium carbonate encrustation but it varies in space and time. This process contributes to water decalcification, impacting water chemistry and carbon cycling in aquatic ecosystems. Charophytes, particularly large species, play a significant role in carbon sequestration through the precipitation and deposition of CaCO3, and this review shows that charophytes can capture and deposit in the bottom sediments up to >300 g C m−2. However, different species exhibit varying degrees of carbonate deposition and recirculation. Therefore, although the hypothesis adopted was supported by the results of this review, further study is needed to fully understand the long-term impact of charophytes on carbon sequestration and the influence of climate change on their growth and permanent CaCO3 deposition.